2022
DOI: 10.1155/2022/3592422
|View full text |Cite
|
Sign up to set email alerts
|

A New Fractional‐Order Map with Infinite Number of Equilibria and Its Encryption Application

Abstract: The study of the chaotic dynamics in fractional-order discrete-time systems has received great attention over the last years. Some efforts have been also devoted to analyze fractional maps with special features. This paper makes a contribution to the topic by introducing a new fractional map that is characterized by both particular dynamic behaviors and specific properties related to the system equilibria. In particular, the conceived one dimensional map is algebraically simpler than all the proposed fractiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…In [25] Liu et al proposed a new fractional discrete sinusoidal map, whereas, the chaos in the fractional Hénon-Lozi type map has been examined in [26]. Gasri et al [27] revealed the rich chaotic dynamics of a novel fractional-order map with infinite line of equilibrium points, while In [28], Khennaoui et al have investigated the chaotic dynamics of a new 2D discrete system without equilibrium points. Furthermore, multistability in fractional discrete chaotic maps has recently received a lot of attention [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…In [25] Liu et al proposed a new fractional discrete sinusoidal map, whereas, the chaos in the fractional Hénon-Lozi type map has been examined in [26]. Gasri et al [27] revealed the rich chaotic dynamics of a novel fractional-order map with infinite line of equilibrium points, while In [28], Khennaoui et al have investigated the chaotic dynamics of a new 2D discrete system without equilibrium points. Furthermore, multistability in fractional discrete chaotic maps has recently received a lot of attention [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…In [13] , a 3D fractional iterated map has been developed, in which this fractional map was shown to have hidden attractors whereas, the chaos in the fractional Hénon-Lozi type map has been examined in [14] . The authors in [15] exhibited the rich chaotic behaviors of a new fractional-order map with an infinite line of equilibria, while In [16] , Khennaoui et al. investigated the chaotic dynamics and combined synchronization of three two-dimensional maps.…”
Section: Introductionmentioning
confidence: 99%